HUBUNGAN POLAl ASUH ORANG TUAl DENGAN PERKEMBANGAN ANAK USIA PRASEKOLAH DI PAUD UMMI PALEMBANG - Sri Hartati; Putinah Putinah (Public Health Department, Faculty of Health Science University Muhammadiyah Bengkulu, 2022)
Background:Palrelnting caln bel intelrprelteld als al delscription of thel alttitudels alnd belhalviors of palrelnts alnd childreln to intelralct, communicaltel during thel conduct of alctivitiels calrelgivelr. Delvellopmelnts is increlalsing thel albility in thel structurel alnd function of thel body morel complelx in thalt relgulalr palttelrn alnd caln bel preldicteld, als al relsult of thel malturaltion procelss. Thel purposel of this study wals to deltelrminel thel rellaltionship palrelnting of palrelnts towalrd childreln delvellopmelnt of prelschool algel childreln alt kindelrgalrteln Ummi Pallelmbalng in 20l1l5. Metodh: Thel delsign of this study qualntitaltivel alnallyticall survely melthod with cross selctionall alpproalch. Thel populaltion of thel study wals thel palrelnts who halvel prelschool childreln alt kindelrgalrteln Ummi Pallelmbalng. Thel salturalteld salmpling melthod wals useld to sellelct thel salmplel. Thel totall numbelr of thel salmplel wals 38 relspondelnts. Result: Thel relsult of univalrialtel stalteld thalt delmocraltic palrelnting 23 (60l.5%), aluthoritalrialn palrelnting 1l0l (26.3%), pelrmissivel palrelnting 5 (1l3.2%) normall childreln delvellopmelnt 22 (57.9%), dubious childreln delvellopmelnt 1l4 (36.8%), albnormall childreln delvellopmelnt 2 (5.3%). From bivalrialtel of palrelnting palrelnts with prelschool algel child delvellopmelnt with ρvalluel 0l,0l0l4 ≤ α 0l.0l5 it melalns thalt thel is correllaltion melalning beltweleln palrelnting of palrelnts towalrd prelschool algel childreln. Conclution : hopeld thalt palrelnt should alpply palrelnting delmocraltic thalt thel delvellopmelnt of childreln will bel belttelr.